(untitled) (Medico Legal Update, 2020)
Objective: The present study aimed to evaluate the effectiveness of communication skills training on the self-efficacy and emotional-social adjustment in the women with MS in Ahvaz. Methodology: This is an experimental study conducted with pretest-posttest design and a control group. The statistical population included the women with MS who referred to the MS Association of Ahvaz. 30 patients with a low score on self-efficacy scale were selected and they were randomly assigned into experimental/ case and control groups. The Multiple Sclerosis Self-efficacy Scaleand Bell Emotional Adjustment Inventory were used to collect the data. MANCOVA was used in order to analyze the data. Results: The results revealed that communication skills training can enhance the self-efficacy of the MS patients and improve their adjustment level (0.001). Conclusion: Training of communication skills can enhance the self-efficacy by improving the patients’ social communication and the level of their communication with the daily external environment.